The Influence of Polygonum Minus Huds on Bacteria to Acrylic Denture - Sri Rezki; Halimah Halimah; Yeni Maryani; Neny Setyowati (Jurnal Kesehatan Gigi, 2020)
The user of acrylic partial denture more than 4,5%  on  Indonesia Country, expecially on West Borneo distrik. Used acrylic partial denture in mouth must be clean, because in the moulth many bacteria. Plaque is a collection of bacteria. Plaque causes of diseases on the teeth and moulth. Plak Cleaning plak using toothbrush and moulthwash. Polygonum minus Huds is the endemic plants in West Borneo. Contained of Polygonum minus Hud are phenolic compounds, flavonoids, alkaloids, steroids, terpenoids, tannins, saponins, and essential oils. It is can antibacterial in the form of Methanol Extract. the purpose of this study was to determine the antibacterial effects of infusion extracts on the collection of bacteria on acrylic denture in the mouth. This study is experimental laboratory research with a posttest only control group design. It was conducted by comparing the antibacterial of Polygonum minus Huds in infusa of 25%, 50%, and 75%. Antibacterial test uses dilution test Antimicrobial Susceptibility Testing (AST). Data analysis uses qualitative data analysis. The results of the study is infusa Polygonum minus Huds can reduce  bakteri colony in acrylic denture. The higher the concentration of the infusa, the higher, the highter antibakteri effect